The Effect of Price and Brand Image on Purchase Intention on Elizabeth Women's Work Bags Products : (Consumer Study in Bandar Lampung) - Miranda Miranda; Satria Bangsawan; Rinaldi Bursan (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
This reseach determine the effect of price and brand image on purchase intention for Elizabeth women's work bag products (a consumer study in Bandar Lampung). Elizabeth women's work bag products were chosen because this brand is quite popular among consumers, known as a long-standing player in the Indonesian bag industry with affordable prices and a positive brand image. The phenomenon underlying this research is the current trend regarding fashion as an important aspect when traveling, as well as a decrease in sales of Elizabeth women's work bag products, which were previously known to hold the first position in the Top Brand Index for the women's work bag category. This study uses a quantitative approach with a survey method through questionnaires distributed online to 120 respondents. The sampling technique used was purposive sampling with the criteria: domiciled in Bandar Lampung, aware of Elizabeth women's work bag products, and having the intention to purchase Elizabeth women's work bag products. Data were analyzed using multiple linear regression with the aid of SPSS. The results show that price and brand image have a significant effect on purchase intention for Elizabeth women's work bag products (Consumer Study in Bandar Lampung). This finding interprets that consumers who intend to buy Elizabeth women's work bag products will consider the factors of price and brand image in making a purchase. Thus, this research can serve as a basis for the Elizabeth brand in setting a competitive price and maintaining its quality or excellence to keep the positive brand image of the product.